Parasites of Fishes Collected from Tigris River, Salah AlDeen Province, Iraq - Al-Nasiri, F. S.; Mhaisen, F. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A total of 109 fish specimens belonging to six species (Barbus grypus, B. luteus, B. xanthopterus, Cyprinion macrostomum, Cyprinus carpio and Liza abu) were collected from Tigris river passing through Salah Al-Deen province during the period from September 2008 till January 2009. These fishes were infected with nine parasite species which included two sporozoans (Myxobolus mÃ¼lleri and Dermocystidium percae), three ciliates (Trichodina cottidarum, T. elegini and T. murmanica) and four monogenetic trematodes (Dactylogyrus rhodeianus, D. vastator, Paradiplozoon cyprini and Microcotyle donavini). Among these parasites, two trichodinids (T. elegini and T. murmanica) were reported for the first time from fishes of Iraq. Also, B. grypus is considered as a new host in Iraq for both D. percae and M. mÃ¼lleri. Apart from D. vastator and P. cyprini, all the remaining seven parasite species were recorded here for the first time from fishes of Salah Al-Deen province. Among the inspected fishes, both B. grypus and L. abu harbored the highest number of parasite species (three each), followed by C. carpio (two parasite species) and B. luteus (one parasite species).